How Should Colleges Treat Multiple Admissions Test Scores?. Issue 3 (25th April 2018) - Mattern, Krista; Radunzel, Justine; Bertling, Maria; Ho, Andrew D.
Abstract: The percentage of students retaking college admissions tests is rising. Researchers and college admissions offices currently use a variety of methods for summarizing these multiple scores. Testing organizations such as ACT and the College Board, interested in validity evidence like correlations with first‐year grade point average (FYGPA), often use the most recent test score available. In contrast, institutions report using a variety of composite scoring methods for applicants with multiple test records, including averaging and taking the maximum subtest score across test occasions ("superscoring"). We compare four scoring methods on two criteria. First, we compare correlations between scores and FYGPA by scoring method. We find them similar ( r ≈ . 40 ). Second, we compare the extent to which test scores differentially predict FYGPA by scoring method and number of retakes. We find that retakes account for additional variance beyond standardized achievement and positively predict FYGPA across all scoring methods. Superscoring minimizes this differential prediction—although it may seem that superscoring should inflate scores across retakes, this inflation is "true" in that it accounts for the positive effects of retaking for predicting FYGPA. Future research should identity factors related to retesting and consider how they should be used in college admissions.